Latent Class Analysis on Suicide-related Behavior and Associated Factors in Korean Adolescents - Eun-Hi Choi, PhD, RN; Suyon Baek, PhD, RN (Elsevier, 2024)
Summary: Purpose: This study aimed to analyze the latent class of suicide-related behaviors among Korean adolescents and identify related factors. Methods: This study used 2021 Korean Youth Risk Behavior Web-Based Survey data and analyzed 7300 participants using latent class analysis. Results: Suicide-related behaviors were categorized into four classes: suicide ideation only (Class 1), suicide plan without ideation or attempt (Class 2), suicide attempt with ideation and plan (Class 3), and suicide attempt without ideation or plan (Class 4). Sexual intercourse experience, habitual drug use experience, and hospital treatment experience due to violence, which were set as risky behavior-related variables, were found to be factors influencing Class 3. However, these variables were not statistically significant factors affecting those belonging to Class 2 and Class 4. Conclusion: The findings emphasize the necessity of understanding the variances in suicide-related behaviors among adolescents to tailor interventions effectively. Adolescents who plan and attempt suicide despite having low levels of suicidal ideation exhibited high levels of stress and a tendency for sadness and despair compared to the suicide attempt with the ideation and plan group. These insights underscore the importance of addressing psycho-emotional factors and developing intervention strategies that cater specifically to the nuanced needs of each group to prevent potential suicide attempts.